Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Media Video Terhadap Pemahaman Konsep Siswa Pada Materi Jamur (Fungi) - Nurjannah, Nurjannah; Khaerati, Khaerati; Anshori, Fitrah Al (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2023)
Based on the results of observations and interviews with biology teachers at SMA Negeri 5 Palopo, it was found that problems that often occur in the teaching and learning process are students who are less active in learning, so a model and learning media are needed. The guided inquiry learning model assisted by video media is an alternative in increasing students' conceptual understanding of mushrooms (fungi). The type in this study used a Quasi Experiment with a Non-equivalent control group design research design. The population in this study were students of Class X SMA Negeri 5 Palopo. The group that was used as a sample was class XMia1 as the experimental class and class XMia2 as the control class. The instrument in this study used a learning achievement test. Data analysis used descriptive and inferential analysis. Inferential analysis using normality test, homogeneity, and hypothesis test. The results showed that the average pretest score for the experimental class was 40.42, while the posttest average score for the experimental class was 84.00. The average value of the control class pretest was 41.52, while the posttest average value of the control class was 80.39. The hypothesis test shows that (2.37 <0.05), it can be concluded that the use of video-assisted inquiry learning models has an effect on students' understanding of concepts in the Fungi subject.Keywords: Guided Inquiry, Videos, Understanding Concepts